2021
DOI: 10.30598//ijcr.2021.8-kur
|View full text |Cite
|
Sign up to set email alerts
|

Study Microstructure of Fe3O4 Modification Using PEG 4000 form Iron Sand at Wari Ino Beach As A Biosensor Application

Abstract: Fe3O4 encapsulated PEG form iron sand at wari ino beach has been successfully synthesized by co-precipitation method. The average particle size  of the nanoparticle 11,3 nm was determined by scherrer formula. Fe3O4 modification PEG 4000 was successfully encapsulated the samples  by the presence C-O-C and CH bonding that were characterized using Fourier Transform Infra Red (FTIR), X-Ray Diffraction (XRD) pattern  shows that all samples  are formed by single  phase cubic spinel magnetite  , and Scanning Electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The element percentages within the nanoparticles are illustrated in Figure 4, with Fe at 51.79% and O at 25.68%, confirming the successful synthesis of Fe3O4 nanoparticles. These EDX findings are consistent with those of Kurnia et al, who reported Fe at 65.86% and O at 19.18% [25].…”
Section: Resultssupporting
confidence: 93%
“…The element percentages within the nanoparticles are illustrated in Figure 4, with Fe at 51.79% and O at 25.68%, confirming the successful synthesis of Fe3O4 nanoparticles. These EDX findings are consistent with those of Kurnia et al, who reported Fe at 65.86% and O at 19.18% [25].…”
Section: Resultssupporting
confidence: 93%
“…Fe elements are 59.7%, and O is 29.61%, which shows that the synthesis of Fe3O4 nanoparticles was successful[24]. The EDX results obtained are following research by Kurnia et al, 2021, which obtained Fe elements of 65.86% and O elements of 19.18%[25].…”
supporting
confidence: 69%
“…This situation shows that the silica has been completely coated on the magnetite surface. Finally, the magnetite detected by the XRD device decreases in intensity (Kurnia, Kaseside, & Iwamony, 2021). at 355-370 cm -1 and 560-580 cm -1 .…”
Section: X-ray Diffractometry (Xrd)mentioning
confidence: 90%